Climate Change Impacts on Cocoa Production in Central America and the Caribbean - Bunn, Christian; Lundy, Mark M.; Wiegel, Jennifer Rebecca; Castro-Llanos, Fabio Alexander (International Center for Tropical Agriculture, 2019)
This document is an atlas of Central America and the Caribbean that provides general information on the different degrees of adaptation effort needed to mitigate the impacts of climate change on cocoa production. It also contains maps of the region, and by country, of agroclimatic zones (ZAC) and of the impact gradient. Information that allows us to better understand the big picture of the region regarding the effects of climate change on cocoa in the region and opens the debate on sustainable practices and investments necessary to address future risks. The map of cocoa presences allows the identification of cocoa production areas; agroclimatic zone maps show future changes in climatic zones suitable for cocoa; The impact gradient maps allow you to identify the level of impact in your area, first in the region and then by country.